Effect of extraction conditions on antioxidant activity and phenolic content in Garcinia Mangostana L. pericarp powder - Ishak, Muhammad Faiz Isyraf (2016)
Garcinia Mangostana L. is a popular subject in both modern and traditional medicinal world. Few studies proved that the ability of the fruit to treat various kinds of infections and diseases comes from abundance of antioxidant inside the fruit mainly at the pericarp. This study was made to understand the effect of time, temperature, solid to solvent ratio towards antioxidant activity and phenol yield and constructing mathematical model of antioxidant and phenol activity in Garcinia mangostana pericarp. Powdered pericarp as the sample undergoes solvent extraction by using two solvents, methanol and ethanol. The solid-and solvent ratio was maintained at 1 g: 50 ml and 1 g: 100 ml. The time and temperature of extraction that are being generated from Design Expert software was in the range of 1-3 hours and 30-60°C respectively. The absorbance was measured using UV-Vis spectrophotometer and the results were being analyzed by DPPH assay for antioxidant activity and Folin-Ciocalteu assay for phenol content. Highest antioxidant yield from methanol was obtained at 3.41 hours extraction time, 23.79°C temperature and 1:100 solid-to-solvent ratio. Highest TPC from methanol was obtained at 3.41 hours extraction time, 23.79°C temperature and 1:100 solid-to-solvent ratio. Extraction from ethanol has the highest antioxidant yield at 3.41 hours extraction, 30°C temperature, and 1:50 solid-to-solvent ratio while TPC yield is the highest at 3.41 hours extraction, 66.21°C temperature, and 1:50 solid-to-solvent ratio. Methanol has higher percent inhibition (80.36%) compared to ethanol (78.53%). Methanol also has higher TPC yield (33.88 mg/ml) than ethanol (31.47 mg/ml). Regression equation of the data was made and optimization was successfully done. Optimized condition for methanol is 57.75°C temperature, 1.03 h extraction time, and 1 g: 50 ml solid-to-solvent ratio while optimized condition for ethanol is 57.74°C temperature, 2.40 h extraction time, and 1g: 50 ml solidto-solvent ratio